Acute intermittent porphyria: A rare cause of hyponatraemia - Mohamed Zainuddin, Nadiah; Sthaneshwar, Pavai; Vethakkan, Shireene Ratna (College of Pathologists, Academy of Medicine Malaysia, 2019)
Introduction: Hyponatraemia is one of the most frequent laboratory findings in hospitalised patients. We present an unusual case of hyponatraemia in a 23-year-old female secondary to acute intermittent porphyria (AIP), a rare inborn error of metabolism. Case Report: The patient presented with upper respiratory tract infection, fever, seizures and abdominal pain. An initial diagnosis of encephalitis was made. In view of the unexplained abdominal pain with other clinical findings such as posterior reversible encephalopathy syndrome by CT brain, temporary blindness as well as hyponatraemia, acute intermittent porphyria was suspected. Urine delta aminolaevulinic acid (δ-ALA) and porphobilinogen were elevated confirming the diagnosis of AIP. Genetic studies were done for this patient. The patient had a complete resolution of her symptoms with carbohydrate loading and high caloric diet. Conclusion: Although rare, AIP should be considered as a cause of hyponatraemia in a patient who presents with signs and/or symptoms that are characteristic of this disease. © 2019, Malaysian Society of Pathologists. All rights reserved.